Building a National Electronic Medical Record Exchange System – Experiences in Taiwan. Issue 1 (August 2015) - Li, Yu-Chuan (Jack); Yen, Ju-Chuan; Chiu, Wen-Ta; Jian, Wen-Shan; Syed-Abdul, Shabbir; Hsu, Min-Huei
Highlights Electronic medical record (EMR) can support a secure, real-time, point-of-care, patient centric information resource for clinical care. Taiwan's government has been promoting the EMR adoption since 2000. We describe the EMR adoption strategies, current progress in EMR development, and our practical experience and lessons learned in implementing the EMR exchange system in Taiwan.